2021
DOI: 10.3390/sym13060914
|View full text |Cite
|
Sign up to set email alerts
|

How Asymmetries Evolved: Hearts, Brains, and Molecules

Abstract: Humans belong to the vast clade of species known as the bilateria, with a bilaterally symmetrical body plan. Over the course of evolution, exceptions to symmetry have arisen. Among chordates, the internal organs have been arranged asymmetrically in order to create more efficient functioning and packaging. The brain has also assumed asymmetries, although these generally trade off against the pressure toward symmetry, itself a reflection of the symmetry of limbs and sense organs. In humans, at least, brain asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 108 publications
1
6
0
6
Order By: Relevance
“…Intriguingly, this idea is very much in line with the "from hand to mouth" theory about the origins of language, proposed by Mike Corballis 20 years ago [30]. Mike Corballis also contributed a theoretical paper to this Special Issue [31]. Entitled "Asymmetry research in human subjects and in non-human species-How Asymmetries Evolved: Hearts, Brains, and Molecules", this article gives a cross-species overview of the evolution of asymmetries in the body and brain, and their potential molecular basis.…”
Section: Theoretical Articlessupporting
confidence: 69%
“…Intriguingly, this idea is very much in line with the "from hand to mouth" theory about the origins of language, proposed by Mike Corballis 20 years ago [30]. Mike Corballis also contributed a theoretical paper to this Special Issue [31]. Entitled "Asymmetry research in human subjects and in non-human species-How Asymmetries Evolved: Hearts, Brains, and Molecules", this article gives a cross-species overview of the evolution of asymmetries in the body and brain, and their potential molecular basis.…”
Section: Theoretical Articlessupporting
confidence: 69%
“…Although no one yet knows for sure how life on earth acquired its asymmetric character or what the biological advantage of asymmetry over symmetry would be [10], some authors suggest that the asymmetry could have a molecular origin from which life would evolve [11][12][13]. If we go back to pure physical concepts, Joe Rosen suggests that symmetry underlies nature [14], but the same author indicated that symmetry implies asymmetry, and that the universe cannot have perfect symmetry [15].…”
Section: The Early Developmentmentioning
confidence: 99%
“…A higher rate of non‐right‐handedness (NRH), which includes left‐ and mixed‐handedness, has been reported for neuropsychiatric and neurodevelopmental conditions, such as schizophrenia, autism, and intellectual disability (Hirnstein & Hugdahl, 2014 ; Markou et al, 2017 ; Papadatou‐Pastou & Tomprou, 2015 ). The underlying hypothesis is that the genetic pathways required for establishing left–right brain asymmetries might also contribute to handedness and be involved in neurodevelopmental conditions (Corballis, 2021 ). It is important to emphasize that the majority of left‐handers are not affected by these conditions and therefore left‐handedness should not be equated to a pathological status.…”
mentioning
confidence: 99%